Implementation Marketing Strategy for Business Start-up: Applications Home Care “4 Care” - Rachmawati Putri Utami; Tantri Yanuar Rahmat Syah; Semerdanta Pusaka; Dadan Ramdhani (Journal of Multidisciplinary Academic, 2020)
Marketing strategy is an effort to develop market product, both of goods and services using a powerful and specific plan also strategy to determine the sales proportion becomes higher. Here, the marketing strategy has an important role in company due to economic value. The purpose of marketing to create a marketing strategy using digital marketing with increasing unique users and applications features to get a revenue according to the marketing targets. One of the marketing strategies is carried out by PT. Rembaka Catur Sekawan on Four Care Application service in the advertising strategy through the social media. Social media was chosen due to most a people use their daily activities for various purposes. In addition, social media was chosen as a advertising platform because it has a wide reach in marketing.